2021
DOI: 10.1111/aphw.12290
|View full text |Cite
|
Sign up to set email alerts
|

Role of received social support in the physical activity of coronary heart patients: The Health Action Process Approach

Abstract: Physical activity (PA) plays a crucial role in the management of coronary artery disease (CAD). The Health Action Process Approach provides a useful framework for understanding and predicting the process of health behaviors. The aim of the current study was to unveil the role of received social support in the HAPA model, concerning the physical activity of CAD patients. A longitudinal sample of 117 CAD patients filled out a questionnaire during three measurement points (baseline, 2 months, and 6 months later).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 73 publications
(105 reference statements)
2
9
0
Order By: Relevance
“…In parallel multiple mediated analyses, first, the social support of patients with CAD had a significant positive correlation with physical activity. This finding was similar to those of previous studies on CAD, which revealed that patients with higher social support from health-care providers showed higher levels of physical activity [ 14 , 17 ]. This finding is supported by previous studies demonstrating that social support is a strong factor affecting physical activity within the CAD population [ 14 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In parallel multiple mediated analyses, first, the social support of patients with CAD had a significant positive correlation with physical activity. This finding was similar to those of previous studies on CAD, which revealed that patients with higher social support from health-care providers showed higher levels of physical activity [ 14 , 17 ]. This finding is supported by previous studies demonstrating that social support is a strong factor affecting physical activity within the CAD population [ 14 , 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…This finding was similar to those of previous studies on CAD, which revealed that patients with higher social support from health-care providers showed higher levels of physical activity [ 14 , 17 ]. This finding is supported by previous studies demonstrating that social support is a strong factor affecting physical activity within the CAD population [ 14 , 26 ]. These results indicate that social support, such as information provision and encouragement by health-care providers, is the driving force behind maintaining and promoting physical activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The volitional phase mainly includes planning and maintaining health behavior changes ( 31 ). This framework has been applied in some studies for CHD patients ( 32 , 33 ). Besides, based on the concept of a care bundle to maximize the intervention effect, the combination of several simple interventions could achieve some measurable effects ( 34 ).…”
Section: Methodsmentioning
confidence: 99%